The role of CD4+ T-cell subsets in determining transplantation rejection or tolerance. - Zelenika, D; Adams, E; Humm, S; Lin, C; Waldmann, H; Cobbold, S (2001)
Peripheral tolerance to allogeneic organ grafts can be induced in rodents by treating with non-depleting CD4 and CD8 monoclonal antibodies. This tolerance is maintained by CD4+ T cells with a potent capacity to induce tolerance in further cohorts of T cells (i.e. infectious tolerance). We have cloned CD4+ T-cell subsets against the male transplantation antigen in vitro and find, in contrast to Th1 or Th2 clones that elicit rejection, that there is a distinct population of CD4+ T cells that suppress rejection by adoptive transfer (here called Treg). In order to identify molecular markers associated with tolerance and gain insights into the mechanisms of action of Treg cells, we carried out serial analysis of gene expression. We identified genes overexpressed in Treg compared to Th1 and Th2 cultures and found that some of these correlated in vivo with CD4-induced transplantation tolerance rather than rejection. The genes overexpressed in Treg cultures and within tolerated skin grafts were primarily expressed by mast cells (e.g. tryptophan hydroxylase and FcepsilonR1alpha), suggesting that regulatory cell activity and this form of tolerance may be associated with a localised but non-destructive form of Th2-like activation and a recruitment of mast cells.